A review and a preleminary study on self absorption correction in gamma-spectrometry / Ahmad Saat - Saat, Ahmad (Universiti Teknologi MARA Cawangan Pahang, 1996)
The article gives a review on self-absorption problem encountered in gamma-ray spectrometry. Various correction methods for different experimental setups were discussed in terms of their approaches and limitations. Assumptions used in deriving the correction models were also listed. Results of a preliminary study was also described.